Platelet rich plasma injections for knee osteoarthritis: an overview of systematic reviews - Yi, Lin; Qiu, Fei; Song, Haiyuan; Huang, Huiyuan; Zhang, Guanghui (Frontiers in Physiology, 2025)
Introduction Knee osteoarthritis (KOA) is a prevalent degenerative joint disease, particularly affecting the aging population. While numerous systematic reviews (SRs) and meta-analyses (MAs) have evaluated the efficacy and safety of platelet-rich plasma (PRP) for KOA, the methodological quality and potential biases of these syntheses require critical assessment.MethodsWe conducted an overview of SRs/MAs on PRP for KOA. Comprehensive searches were performed in PubMed, Embase, The Cochrane Library, and Web of Science from inception to December 1, 2024. Two reviewers independently screened literature and extracted data. The methodological quality of included SRs/MAs was evaluated using AMSTAR-2, the degree of primary study overlap was assessed using the GROOVE tool, and the risk of bias in the primary randomized trials was evaluated using the ROB 2.0 tool.ResultA total of 29 SRs/MAs met the inclusion criteria. GROOVE analysis revealed a very high degree of overlap among the primary studies included across the reviews. AMSTAR-2 assessment demonstrated critically low methodological quality for 26 reviews and low quality for the remaining 3 reviews.DiscussionThe current quality of SRs/MAs on PRP for KOA remains suboptimal. Future studies should adhere closely to established evaluation frameworks including AMSTAR2 to enhance research reliability and clinical applicability.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024619416.